Unmasking Reflexivity in HR Managers During the COVID-19 Lockdown in Italy - Ripamonti, Silvio Carlo (Front Psychol, 2020)
This paper explores how some Italian HR managers narrate the changes imposed by the COVID-19 threat in the workplace. Events since December 2019 have presented exceptional circumstances to which HR managers have reacted in very different ways. This study explored how HR managers came to introduce organizational changes aimed at coping with the emergency, as well as how employees were involved in those organizational changes. The article is based on a thematic analysis of some interviews with Italian HR managers whose companies decided to switch working from home on a massive scale. We wanted to offer some reflections on the actions taken by a few HR managers and Italian companies to keep working at a time when most workers were forced to respect the lockdown.